The Influence of FASD on Psychiatric Disorders: A Literature Review on the Mechanisms Relating Fetal Alcohol Spectrum Disorders to Mental Health Conditions in Adulthood - Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Dubniewicz, Ewa; Majewska, Paula; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof (Journal of Education, Health and Sport, 2025)
The Fetal Alcohol Spectrum Disorders (FASD) encompass a variety of physical, behavioral and neurological disorders resulting from fetal alcohol exposure. FASD includes full Fetal Alcohol Syndrome (FAS), partial FAS (pFAS), Alcohol-Related Neurodevelopmental Disorder (ARND) and Alcohol-Related Birth Defects (ARBD). It is estimated that there is an average of 7.7 cases per 1000 people worldwide. Despite its frequent occurrence, FASD is often underdiagnosed what results in affected patients do not receive appropriate assistance and care that would mitigate its negative effects. Alcohol is a toxic substance for the developing fetus, and its impact depends on factors such as the amount of alcohol consumed, the timing of exposure, and individual genetic predispositions. Fetal Alcohol Spectrum Disorder (FASD) is a significant and preventable cause of birth defects and developmental disorders. The multifactorial mechanisms linking FASD with psychiatric disorders include neurobiological damage, chronic neuroinflammation, and environmental influences. This article highlights the urgent need for global prevention programs and education on the harmful effects of alcohol consumption during pregnancy. It also suggests further research into epigenetic and neuroprotective therapies to reduce the risk of psychiatric disorders in individuals affected by FASD.